IMPACT OF ART AND ARCHITECTURE IN THE MODERN WORLD AND ITS SURROUNDINGS - Naaz, Shaila; Thongamcha, Loyangamba (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Architecture has been amongst the fundamental cornerstones that have moulded society for centuries. The element of art in architecture further enhances its influence on those who perceive the architectural piece. The purpose of this research is to carefully scrutinize powerful examples of architecture from history and learn about their role in influencing human emotions, societal norms, cultural identity and economic and political landmarks. The chief objective of this study is to learn about the vitality of art and architecture in impacting various tenets of human experiences. The author makes use of relevant literature and examples from all around the globe and varying time periods with the aim to appreciate the subtle yet monumental role of architecture in shaping the world around us. A thorough account of architectural ideology and works from Nazi Germany and the impact of the destruction of the World Trade Center in New York highlights the undeniable role played by architecture in influencing the lived experiences of humans.